The Role of Transformational Leadership Style on Employee Engagement and Organizational Innovation in the Hybrid Work Era - Nasution, Siti Ummi Arfah; Sibuea, Nurhalimah (PT Inovasi Pratama Internasional, 2025)
This study explores the role of transformational leadership in enhancing employee engagement and fostering organizational innovation within the context of hybrid work arrangements. Using a qualitative research approach, data were collected through in-depth interviews and focus group discussions with organizational leaders and employees operating in hybrid work environments in Indonesia. The findings reveal that transformational leaders, through inspirational motivation, individualized consideration, intellectual stimulation, and idealized influence, significantly contribute to higher levels of employee engagement and promote innovative behaviors despite the challenges posed by hybrid work settings. The study underscores the importance of adaptive leadership practices to sustain organizational competitiveness in the evolving work landscape.